IDDF2019-ABS-0151 Clinical utility of endoscopic retrograde appendix stenting in the oldest-old patients. (June 2019) - Wu, Jia-Chuan; Liang, Biao; Yang, Xiao-Qiao; Chen, Rui-Yan; Chen, Xiao-Dong; Ye, Li-Fang
Abstract : Background: To evaluate the indications, efficacy, safety and recurrence rate of endoscopic retrograde appendix stenting for the oldest-old patients aged 80 and over. Methods: Data of the oldest-old patients who went through endoscopic retrograde appendix stenting in our center between July 1st, 2017 and June 30th, 2018 were retrospectively analyzed. The endoscopic procedures included 4 steps: (1) colonoscopic appendiceal intubation, (2) retrograde appendicography, (3) stent drainage and appendiceal decompression, (4) stent extraction 2 weeks later. Main outcome measurements included successful colonoscopic intubation rates, the time to symptom relief, the time to abdominal sign disappearance, increased white blood cell count, procedure-related complications, and recurrence. Results: 6 patients were enrolled in our study. No immediate endoscopy-related complications and death occurred. All colonoscopic appendiceal intubations were successful. The pain of oldest-old patients was relieved immediately after endoscopic procedures. Abdominal signs, such as tenderness and rebound tenderness, disappeared within 12–24 hours. The increased white blood cell count returned to normal within 24–48 hours. 5 patients had endoscopic stent extraction 2 weeks later, while one had stent migration and extrusion spontaneously. Normal morphology of the appendix opening was observed in all patients at the review. And there were no recurrences during 9–18 months of follow-up. Conclusions: Endoscopic retrograde appendix stenting is feasible, safe and effective. With less trauma and quick recovery, it is a treatment of appendicitis that particularly suited to the oldest-old patients.